Investigation of the Cognitive Attitudes and Behaviors of Medical Post-graduates in Clinical Practice During the COVID-19 Pandemic in China - Feng, Lei; Xie, Zefeng; Shen, Junhui (Frontiers in Public Health, 2021)
The cognitive attitudes and behaviors of medical postgraduates may be influenced by the coronavirus disease 2019 (COVID-19) pandemic. A cross-sectional study was used from a questionnaire survey in hospitals affiliated with the Zhejiang University School of Medicine. Questionnaire was distributed online including demographic information, cognitive attitudes, and personal protective behaviors. Moreover，personal protective behaviors such as wearing protective equipment were compared between different academic major and gender, respectively. A total of 176 valid questionnaires were obtained. Of the medical postgraduates in this study, (1) 89.67% believed that the COVID-19 pandemic had an impact on their clinical internships, and 40.34% expressed concerns about their infection on inadequate personal protection; (2) 91.48% took personal protection in hospital and 86.36% enhanced personal hygiene; (3) There were no statistically differences in the personal protection by academic major and gender (p > 0.05). This study suggests that the COVID-19 pandemic had an impact on the medical postgraduates’ clinical practice, and affected their cognitive attitudes and behaviors. As such, universities and hospitals should increase pandemic prevention training and investment, provide more psychological counseling to their medical postgraduates to reduce their psychological burden, and take measures to reduce the influence of the COVID-19 pandemic on their medical postgraduates’ clinical practice.